1987
DOI: 10.1136/bmj.295.6601.745
|View full text |Cite
|
Sign up to set email alerts
|

The natural course of gold nephropathy: long term study of 21 patients.

Abstract: To clarify the natural course of gold nephropathy and thereby facilitate its clinical management 21 patients with rheumatoid arhritis who developed proteinuria during treatment with intramuscular sodium aurothiomalate were studied in detail throughout their renal illnesses. Renal biopsies were performed, and creatinine clearance and protein were measured serially for 60 months (range 16-130 months). Ten patients developed proteinuria after six months' treatment, 15 after 12 months, and 18 after 24 months. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

1988
1988
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 10 publications
1
45
0
2
Order By: Relevance
“…Renal biopsy most commonly reveals stage 1 or 2 MN, indicating early detection because of screening. After withdrawal, proteinuria resolves in most patients (106,108). Experimental studies have shown that gold inclusions mainly localize to proximal tubules, and the same is true in a rodent model of goldinduced MN, suggesting that gold targets tubular epithelia and leads to release of tubular antigens that cross-react with podocyte antigens, akin to the mechanism of Heymann nephritis (109,110).…”
Section: Drugs Associated With Mnmentioning
confidence: 92%
“…Renal biopsy most commonly reveals stage 1 or 2 MN, indicating early detection because of screening. After withdrawal, proteinuria resolves in most patients (106,108). Experimental studies have shown that gold inclusions mainly localize to proximal tubules, and the same is true in a rodent model of goldinduced MN, suggesting that gold targets tubular epithelia and leads to release of tubular antigens that cross-react with podocyte antigens, akin to the mechanism of Heymann nephritis (109,110).…”
Section: Drugs Associated With Mnmentioning
confidence: 92%
“…Mesangial glomerulonephritis presenting with pro teinuria has been detected during gold [16,17] or DPA [18] therapy. In our study, proteinuria was clinically closely related to the use of GSTM, DPA or auranofin in 5 out of 6 patients with isolated proteinuria and in 4 out of 7 patients with hematuria combined with proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…The severity and duration of the proteinuria vary greatly [8,13] and are not related to the total dose of gold received, the duration of treatment, the peak or mean serum gold levels or the urinary gold excretion [6,14]. In a recent study [13], although the severity of proteinuria varied widely (0.6-30.7 g/day), the median initial and maximum pro teinuria were 1.7and2.0g/day, respectively. In halfofthe patients the initial proteinuria was also the maximum whilst in the remainder the proteinuria increased for 1-13 months (median 4 months) after gold treatment had been stopped.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The incidence of proteinuria observed during gold treatment has varied between 1 and 10% [1][2][3][4][5][6] with occa sional reports of more than 20% [7], Proteinuria occurs in patients of both sexes, at all ages (2-73 years) and in association with all parenteral soluble gold preparations (thiomalate, thiosulphate, thioglucose, phenylphosphinic acid) [8,9] and with oral gold treatment (auranofin) [5], Proteinuria Although proteinuria may develop at any time from 2 weeks (10 mg) to more than 6 years (6,000 mg) during treatment [6,[10][11][12], in some 50% of patients the onset occurs in the first 6 months of treatment, in 70% by 12 months and in 85% by 24 months with a peak incidence (40%) in the second 3 months of treatment [13]. The severity and duration of the proteinuria vary greatly [8,13] and are not related to the total dose of gold received, the duration of treatment, the peak or mean serum gold levels or the urinary gold excretion [6,14].…”
Section: Clinical Featuresmentioning
confidence: 99%